Cartografando as performances do professor (2018)
This article aims to outline a brief mapping of different educational performances on the teaching practice in the classroom. This mapping is part of the research carried out during the Masters degree in PPG - IA / UNESP, entitled “Adote um artista não deixe ele virar professor: reflexões em torno do híbrido professor performer”, which aims to provoke questions about how teachers transiting between different education paradigms to constitute ourselves as such, to exercise the craft of art education in the context of formal education. Therefore, I propose a dialogue with the conceptions of profesor-prophet, in a study of Silvio Gallo’s writings; professor-artist, from the perspective of Elyse Lamm Pineau; and professor-performer, developed by Naira Ciotti as possible focus to an initial investigation of teachers performativities.